EVALUASI KEMAMPUAN LAHAN PADA LAHAN TANAMAN CENGKEH DAN KAKAO MENUJU PERTANIAN BERKELANJUTAN - Nia Rulinggar Putri M; Eko Setiyo Wawan; Robithotul Ummah; Sri Wiyatiningsih (Universitas 17 Agustus 1945 Samarinda, 2022)
The research purposed to know the land capability class and study the Sustainable Agricultural Management with Agroforestry systems on the land of PT. Fructi Agri Sejati Dusun Komboh, Sambirejo Village, Kec. Wonosalam, Kab. Jombang. One of the ways to manage sustainable agricultural land is by utilizing land according to the land capability class. Land use must be balanced between land use and conservation efforts to maintain the balance of the ecosystem and the preservation of the physical condition the land. The application of agroforestry systems have included one way of the sustainable agricultural systems. The results showed that the land capability class for Clove and Cocoa was class VI with limiting factor is the slope. Land use based on land capability class for clove and cocoa plants, are: 1) Nature Reserve, 2) Forestry, 3) Limited grass, and 4) Fairly good grass. The land use is sought to be as close as possible to the characteristics of the nature reserve and to adjust the slope level, by mechanical and vegetative conservation.